Role of Investment and Macroeconomic Variables on Unemployment in Indonesia - Weni Hawariyuni; Monika Andrasari (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2022)
This study aims to analyze the effect of Foreign Direct Investment (FDI), domestic investment, and other macroeconomic variables towards decreasing unemployment rate in Indonesia. The macroeconomic variables applied in this study composed of inflation, Gross Domestic Product (GDP), Provincial minimum wage, and poverty. This study employed Ordinary Least Squares (OLS) model and panel data from 2010 – 2020 for 34 provinces in Indonesia. This study indicated that GDP and FDI play crucial role in decreasing number of unemployment rate in Indonesia. These two independent variables had negative and significance relationship with number of unemployment rate in Indonesia. It means that if GDP and FDI raise led decreasing on number of unemployment rate in Indonesia. Meanwhile, domestic investment and other macroeconomic variables including inflation, provincial minimum wage, and poverty indicated having insignificant relationship with number of unemployment rate in Indonesia. This study concluded that GDP and FDI have important role in decreasing numbers of unemployment in Indonesia. It means that if GDP and FDI raised significantly causing more job opportunities for unemployment in Indonesia. This study is expected to give contribution for Indonesia Government and Economic policy makers to minimize numbers of unemployment in Indonesia.